E- Government Service Review In Dumai City Indonesia: Conceptual Paper - Afrizal, Dedy (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2020)
Electronic government are in their early stages in many city in Indonesia. Local government has faced a number of challenges and faced with various issues pertaining to their implementation of e-government services. This paper utilises the Unified Theory of Acceptance and Use of technology (UTAUT) model to explore e-government services in Dumai city. The purpose of this paper to present a concept idea to seeing intention to use e-government in Dumai City. The Paper suggest future research with quantitative approach to find aspect to consider in producing significant and credible research findings. This research is expected can help government in improving intention citizens’ use of e-government services. Keywords: E-Government, UTAUT model, Local Government